2012
DOI: 10.1002/cnm.2523
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian analysis of hemodynamics data from FSI simulation

Abstract: We present the computation of Lagrangian-based flow characterization measures for time-dependent, deformable-wall, finite-element blood flow simulations. Applicability of the algorithm is demonstrated in a fluid–structure interaction simulation of blood flow through a total cavopulmonary connection (Fontan procedure), and results are compared with a rigid-vessel simulation. Specifically, we report on several important Lagrangian-based measures including flow distributions, finite-time Lyapunov exponent fields,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 87 publications
1
21
0
Order By: Relevance
“…4A, have negligible influence to particle distributions. Notably, we have previously investigated particle tracking from velocity data of rigid vs. distensible patient-specific vascular models (11) and have observed that vessel compliance has relatively negligible change to transport patterns. Based on these considerations, the rigid-wall assumption employed here for velocity field modeling is expected to have minimal influence to observed distribution patterns and to the main conclusions of this study.…”
Section: Discussionmentioning
confidence: 99%
“…4A, have negligible influence to particle distributions. Notably, we have previously investigated particle tracking from velocity data of rigid vs. distensible patient-specific vascular models (11) and have observed that vessel compliance has relatively negligible change to transport patterns. Based on these considerations, the rigid-wall assumption employed here for velocity field modeling is expected to have minimal influence to observed distribution patterns and to the main conclusions of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the discrete size of the integration time step, a small percentage of particles could erroneously be lost through the wall boundaries. Following the procedure reported in Duvernois et al [33], we added a small inward velocity component of magnitude 1 cm s −1 to the otherwise zero velocity vector at the wall nodes to limit the leakage of particles without significantly affecting the tracking.…”
Section: (E) Particle Tracking and Platelet Activationmentioning
confidence: 99%
“…Changes in AAA hemodynamics between a Newtonian and a non-Newtonian model have been investigated (9), but differences in WSS did not appear compelling. Difference in hemodynamics due to wall motion have also been investigated (15) and found to be negligible when radial strains were less than Ϸ8%. Radial strains were observed to be Ͻ5% from the PCMRI data for the AAAs considered.…”
Section: H1791 Hemodynamics Vs Thrombus Growth In Aaamentioning
confidence: 99%